2019
DOI: 10.1111/sed.12615
|View full text |Cite
|
Sign up to set email alerts
|

Diagenetic controls on the isotopic composition of carbonate‐associated sulphate in the Permian Capitan Reef Complex, West Texas

Abstract: Late Palaeozoic-age strata from the Capitan Reef in west Texas show faciesdependent heterogeneity in the sulphur isotopic composition of carbonateassociated sulphate, which is trace sulphate incorporated into carbonate minerals that is often used to reconstruct the sulphur isotopic composition of ancient seawater. However, diagenetic pore fluid processes may influence the sulphur isotopic composition of carbonate-associated sulphate. These processes variously modify the sulphur isotopic composition of incorpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
40
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 94 publications
(214 reference statements)
3
40
1
Order By: Relevance
“…Diagenetic processes may exchange sulfate with the primary carbonate and alter its isotopic composition (Fichtner et al, 2017;Murray et al, 2020;Present et al, 2015Present et al, , 2019. Kampschulte & Strauss (2004) suggested that the variability of multiple δ 34 S analyses from contemporaneous stratigraphic successions could be used to quantify the effect of diagenesis on the CAS record.…”
Section: Carbonate-associated Sulfatementioning
confidence: 99%
See 4 more Smart Citations
“…Diagenetic processes may exchange sulfate with the primary carbonate and alter its isotopic composition (Fichtner et al, 2017;Murray et al, 2020;Present et al, 2015Present et al, , 2019. Kampschulte & Strauss (2004) suggested that the variability of multiple δ 34 S analyses from contemporaneous stratigraphic successions could be used to quantify the effect of diagenesis on the CAS record.…”
Section: Carbonate-associated Sulfatementioning
confidence: 99%
“…Further, CAS analyses may be contaminated by sulfur from co-occurring phases, including sulfide and disulfide minerals, sulfur-bearing organic material, and sulfate salts (Edwards et al, 2019;Marenco, Corsetti, Hammond, et al, 2008;Present et al, 2015;Theiling & Coleman, 2015;Wotte et al, 2012). Recent application of plasma-source mass spectrometry for sulfur isotope analysis has permitted δ 34 S analyses on less than one-thousandth as much sulfate, corresponding to 5 mg to 50 mg of carbonate Paris et al, 2013;Present et al, 2015Present et al, , 2019Rennie et al, 2018). Well-preserved biogenic grains, recrystallized grains, matrix, and cements contain CAS with δ 34 S compositions varying by as much as 25‰, spanning most of the range of CAS analyses from the entire Phanerozoic (Present et al, 2015(Present et al, , 2019.…”
Section: Carbonate-associated Sulfatementioning
confidence: 99%
See 3 more Smart Citations